Microscale temperature and SAR measurements in cell monolayer models exposed to millimeter waves. Issue 1 (29th August 2016) - Zhadobov, Maxim; Alekseev, Stanislav I.; Sauleau, Ronan; Le Page, Yann; Le Dréan, Yves; Fesenko, Evgeny E.
Abstract : Due to shallow penetration of millimeter waves (MMW) and convection in liquid medium surrounding cells, the problem of accurate assessment of local MMW heating in in vitro experiments remains unsolved. Conventional dosimetric MMW techniques, such as infrared imaging or fiber optic (FO) sensors, face several inherent limits. Here we propose a methodology for accurate local temperature measurement and subsequent specific absorption rate (SAR) retrieval using microscale thermocouples (TC). SAR was retrieved by fitting the measured initial temperature rise to the numerical solution of an equivalent thermal model. It was found that the accuracy of temperature measurement depends on thermosensor size, that is, the smaller TC, the more accurate the temperature measurement. SAR determined using TC with lead diameters of 25 and 75 μm demonstrated 98.5% and 80.4% match with computed SAR, respectively. However, both TC provided the same temperature rises in long run (> 10 min). FO probe failed to measure adequately local heating both for short and long exposures due to the relatively large size of the probe sensor (400 μm) and time constant (0.6 s). Calculated SAR in the cell monolayer was almost two times lower than that in the surrounding liquid. It was shown that the impact of the cell monolayer on heating due to its small thickness (5 to 10 μm) can be considered as negligible. Moreover, we demonstrated the possibility of accurate measurement of MMW‐induced thermal pulses (up to 10 °C) using 25 μm TC. Bioelectromagnetics. 38:11–21, 2017. © 2016 Wiley Periodicals, Inc.